2006
DOI: 10.1189/jlb.1105625
|View full text |Cite
|
Sign up to set email alerts
|

It takes nerve to tell T and B cells what to do

Abstract: The existence of an association between the brain and immunity has been documented. Data show that the nervous and immune systems communicate with one another to maintain immune homeostasis. Activated immune cells secrete cytokines that influence central nervous system activity, which in turn, activates output through the peripheral nervous system to regulate the level of immune cell activity and the subsequent magnitude of an immune response. In this review, we will focus our presentation and discussion on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
175
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(182 citation statements)
references
References 106 publications
3
175
1
3
Order By: Relevance
“…The effect of NE-depletion on the primary T cell-dependent antibody response in vivo has also been investigated [reviewed extensively in (Kin and Sanders, 2006;Kohm and Sanders, 2001b;Sanders and Munson, 1985;Sanders and Straub, 2002)]. Data have shown that either a decrease or increase in the Th cell-dependent IgM antibody response occurs after NE depletion.…”
Section: B Lymphocytesmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of NE-depletion on the primary T cell-dependent antibody response in vivo has also been investigated [reviewed extensively in (Kin and Sanders, 2006;Kohm and Sanders, 2001b;Sanders and Munson, 1985;Sanders and Straub, 2002)]. Data have shown that either a decrease or increase in the Th cell-dependent IgM antibody response occurs after NE depletion.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…Thus, it is difficult to conclude the effect of NE-depletion on the IgM and IgG response in vivo, although most data indicate suppression, suggesting that NE may be needed to play a positive role in an antibody response in vivo, but the mechanisms by which this occurred are beginning to become clearer The finding in vivo that NE-depleted mice were unable to upregulate CD86 expression on B cells when compared to NE-intact mice suggested that CD86 may be regulated by NE to help enhance the antibody response, possibly via co-stimulation of the T cell. But, when examined in vitro, β 2 AR stimulation on a B cell at the time of B cell activation, in the presence or absence of a T cell, directly increased the level of CD86 expressed on, and IgG1 produced by, a B cell [reviewed extensively in (Kin and Sanders, 2006). The β 2 AR-and CD86-induced increase in IgG1 occurred on a per cell basis by increasing the rate of mature IgG1 mRNA production.…”
Section: B Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Circulating t-cell numbers and function are influenced by brief periods of exercise [6,7], and a number of mechanisms have been proposed to explain these effects. First, as noted, exercise alters circulating factors and mediators (e.g., lactate, IL-6, catecholamines, growth hormone) that can affect t-cells [8][9][10]. Secondly, lymphocytes could be influenced by more direct effects such as exercise associated neurostimulation of lymph nodes and other lymph tissues [11,12].…”
Section: Introductionmentioning
confidence: 99%